THE INFLUENCE OF LEADERSHIP STYLE, JOB SATISFACTION AND LOYALTY ON VILLAGE OFFICIAL PERFORMANCE - Risma Lempang; Junaidi Junaidi; Ibrahim Halim (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to determine the effect of leadership style, job satisfaction, and loyalty on the performance of village officials. This study was conducted on Mario village officials and Buntu Kamiri village officials. The method used was through the distribution of questionnaires to respondents. Data were analyzed using Structural Equation Modeling (SEM), a multivariate analysis technique that allows simultaneous examination of complex relationships between observed and latent variables. Multivariate analysis is to analyze the influence of independent variables with dependent variables. This research has several limitations that need to be considered. First, the study only included two villages (Mario and Buntu Kamiri), so the results may not be fully generalizable for the context of other villages. Second, the quantitative approach used in this study focuses on numerical data, so it does not explore more in-depth psychological or social aspects related to job satisfaction and loyalty. Third, the subjectivity or bias of the respondents may influence the data obtained through questionnaires. For future research, it is recommended to expand the research sample to include more villages in different regions so that the results are more representative. Keywords :Leadership Style; Job Satisfaction; Loyalty